Implementasi Metode Diskusi dan Resitasi dalam Meningkatkan Prestasi Belajar Mata Pelajaran PKn Siswa Kelas V SDN Ambat - Riyadi, Selamet (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
This research is aimed to know (1) How is the implementation of Discussion and Recitation method in improving students’ activeness in learning PKn? and (2) is the application of Discussion and Recitation method able to improve students’ achievement in learning PKn?. This research uses Classroom Action Research. Data of the research are collected by using observation and field note and are analysed through data reduction, inference, follow up, and conclusion drawing. The result of the research shows that Discussion and Recitation method is able to improve students’ activeness in learning PKn. The students’ activeness in learning PKn is stimulated through giving appreciation as well as giving additional scores to active students during the discussion proses. this condition is proved by the fluency of the students in learning, writing, memorizing PKn learning materials being discussed in settled groups. Thus, it can be concluded that application of Discussion and Recitation method can improve students’ activeness and students’ achievement in learning PKn in SDN Ambat Kecamatan Janapria Kabupaten Lombok Tengah in academic year 2015/2016. Therefore, it is suggested that teachers implement Discussion and Recitation method in teaching PKn towards students elementary